2013
DOI: 10.1021/om3011855
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on Stoichiometric and Catalytic Cleavage of Carbon–Nitrogen Bonds in Aniline Derivatives by Ruthenium–Phosphine Complexes

Abstract: The reactivity of various o-acylaniline derivatives with ruthenium complexes was examined. The reaction of o-acylanilines with RuH2(CO)(PPh3)3 (1) or an activated ruthenium species formulated as “Ru(CO)(PPh3)3” (4) gave amido hydrido complexes 3 and aryl amido complexes 6 formed via N–H and C–N bond cleavage, respectively. Addition of olefins, such as vinylsilanes, accelerates the C–N bond cleavage. The aryl amido complexes 6 can provide the C–N arylation product upon treatment with arylboronates. The relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 48 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…The lower reactivity of the bonds with better leaving groups is not commonly observed for bond‐cleavage reactions by oxidative addition. The reason for the observed trend is unclear, but it can be explained by considering that smaller, more‐electron‐donating groups coordinate to the metal center more easily to increase the chances of being cleaved by oxidative addition, as observed for our previously reported aromatic CN bond cleavage by a ruthenium center 6c…”
Section: Methodsmentioning
confidence: 82%
“…The lower reactivity of the bonds with better leaving groups is not commonly observed for bond‐cleavage reactions by oxidative addition. The reason for the observed trend is unclear, but it can be explained by considering that smaller, more‐electron‐donating groups coordinate to the metal center more easily to increase the chances of being cleaved by oxidative addition, as observed for our previously reported aromatic CN bond cleavage by a ruthenium center 6c…”
Section: Methodsmentioning
confidence: 82%
“…Further studies indicated that stronger C–N and C–O bonds can also be activated by the same method. In 2004, Kakiuchi et al reported the first ketone-directed Ru-catalyzed C–O bond functionalization (eq 3 ), , also using aryl Bneop as the nucleophile.…”
Section: Introductionmentioning
confidence: 98%
“…In this case, the oxidative transformation of tertiary anilines into N -arylamides was necessary, and the process to cleave aromatic C–N bonds was facilitated by the electron-withdrawing effect of the acyl group, and the π-extended aromatic ring containing substrates showed better reactivity (Scheme b). Kakiuchi and co-workers successfully applied a directing strategy into C–N bond activation to cleave aromatic C–N bonds of tertiary anilines via ruthenium-catalyzed Suzuki–Miyaura cross-coupling with the clear understanding of the catalytic mechanism . The introduction of the acyl group at ortho -position not only played a role as a directing group but also possibly activated the C–N bonds as an electron-withdrawing group (Scheme c).…”
mentioning
confidence: 95%